A Systematic Literature Study on the Avoidance of Decision-Making: A PRISMA Approach - Muhammad Atiq Rafique Khattak; Mohammad Daud Ali; Markus A. Launer (International Journal of Business and Economic Affairs, 2025)
The avoidance of decision-making and role of intuition in decision making has been overlooked in research. The current paper is intended is to lay a better theoretical foundation for empirical research. Recently focus has drawn to the avoidance decision making as decision-making style (Launer and Cetin, 2025). However, the topic needs to be deepened to better understand the reasons for not taking decisions. A PRISMA Study was performed to systematically search for relevant literature in Google Scholar, PubMed, Scopus, Web of Science, and PsycINFO. Out of initially found n = 982 literature sources, n=52 sources were examined. As a result, an improved theoretical literature base is presented as well as a measurement instrument ready to be tested in empirical studies.